The relevance of extensional rheology on electrospinning: the polyamide/iron chloride case. (February 2016) - Formenti, Susanna; Castagna, Rossella; Momentè, Roberto; Bertarelli, Chiara; Briatico-Vangosa, Francesco
Graphical abstract: Highlights: Electrospinning of PA6 and FeCl3 in formic acid correlates with rheological behavior. Being above critical concentration for entanglements does not ensure spinnability. Additivation of the feed solutions must ensure a fluid elasticity dominated process. Addition of FeCl3 to PA6 in formic acid solutions decreases fibre crystallinity. Completely amorphous fibres are formed above a critical concentration of FeCl3 . Abstract: The outcomes of the electrospinning of polyamide 6 (PA6) solutions in formic acid containing FeCl3 are correlated with the extensional rheological behaviour of these fluids, which is investigated by the self-controlled capillary breakup of a filament. The rheological analysis enlightens a significant effect of the FeCl3 content on the rheological behaviour, the viscous component becoming predominant over a certain salt content threshold. At this concentration, the electrospun fibres show the formation of severely inhomogeneous structures this indicating that an elastically dominated behaviour is necessary to yield defect-free fibres. Addition of FeCl3 also decreases fibre crystallinity and fibres turn out to be completely amorphous above a critical concentration. Interestingly, this concentration coincides with the one at which the viscous component starts dominating the rheological behaviour.